Implementasi Manajemen Pendidikan Kewirausahaan dalam Mewujudkan Siswa yang Mandiri di MAN 2 Langkat - Siti Rahma; Ahmad Zaki; Khairani Sakdiah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the implementation of entrepreneurship education management in achieving independent students at MAN 2 Langkat. The research uses a qualitative method with a descriptive approach, employing data collection techniques of observation, interviews, and documentation. The findings show that the planning of entrepreneurship education at MAN 2 Langkat is designed with the aim of equipping students with practical skills and independence. This entrepreneurship program includes various practical activities such as Market Day and bazaar exhibitions, providing students with the opportunity to plan and manage their own businesses. The implementation of the program has proven effective in developing students' entrepreneurship skills, such as business planning, capital management, and product marketing. Evaluation of the entrepreneurship program shows positive impacts, with assessments focused not only on the final results but also on the processes students undergo, including initiative, responsibility, and teamwork. However, several aspects still require improvement, such as financial management and enhancing cooperation among students. Overall, this entrepreneurship program has successfully created independent students, ready to face the challenges of the business world.